Molecular Mechanism of Necroptosis in Macrophages - Yadav, Sahil (Université d'Ottawa | University of Ottawa, 2025)
Regulated cell death plays a vital role in tissue homeostasis and development. Recent studies have highlighted necroptosis, a programmed cell death mode combining features of necrosis and apoptosis, as having diverse biological impacts. The necroptosis pathway involves activating receptor-interacting protein kinases (RipK-1 and -3), which form a complex with mixed-lineage kinase domain-like protein (MLKL). This complex translocates to the plasma membrane, inducing its rupture. This study reveals that ARF6 targets the RipK1-dependent ripoptosome and necrosome cell death pathways without impacting apoptosis susceptibility. ARF6 regulates the maturation of the endo-lysosomal compartment, promoting cIAP1/2 degradation and facilitating RipK1 phosphorylation towards cell death pathways. This finding unveils a new signaling event preceding RipK1 phosphorylation, which is necessary for activating RipK1-dependent cell death pathways. The research also demonstrates that necroptosis program initiation activates RipK1, leading to MAPK pathway upregulation and increased inflammatory cytokine expression, independent of cell death. This inflammatory response is counterbalanced by type I interferon expression during necrosome activation. The crosstalk between IFNAR1 signalling, the MAPK pathway, and post-transcriptional regulation through ZFP36 plays a crucial role in balancing inflammatory responses and cell death. Furthermore, the study provides compelling evidence for IFNAR1 signalling’s critical role in necroptosis. Ifnar1-deficient macrophages exhibit significant resistance to necroptosis induced by various stimuli. IFNAR1 signaling is crucial for the proper functioning of the ISGF3 complex and the expression and activation of MLKL, a key necroptosis executioner. Surprisingly, restoring MLKL expression in Ifnar1-deficient cells did not fully reverse their necroptosis resistance, suggesting additional mechanisms at play. Further investigation revealed that IFNAR1 signaling is essential for the appropriate translocation of phosphorylated MLKL to the plasma membrane, a critical step in necroptosis execution. These findings significantly advance our understanding of the molecular mechanisms underlying necroptosis and highlight the complex interplay between different pathways that lead to programmed cell death pathways in macrophages. Deregulation of necroptosis is associated with pathological conditions such as cancer, neurodegenerative diseases, inflammatory diseases, and critical response against many viruses, including pox, herpes, and influenza. This research aims to identify potential therapeutic targets that can be exploited in chronic inflammatory conditions and viral infections.
Keywords: Necroptosis; Macrophages